Rumpelstiltskin Revisited, Part 2 - Khan, Steven (Daily Express, 2009)
Part 2 of this article seeks to go beyond the allegory of moral virtue and the necessary conditions for building an ethical society covered in the first part of the article to a consideration of some of the other themes found in the story of "Rumpeltstiltskin." It identifies the act of transubstantiation (spinning straw from gold) as a metaphor for the misuse of nature to create wealth, as well as the leitmotif of the power of one's name and the power that other people have in naming us as two important issues treated in the story
Keywords: Resources management; Identification (psychological)